The Role of Buntari Ceramic Studio in Preserving the Pagerjurang Pottery Tradition - Sekar Kinanthi; Yuniana Cahyaningrum (Yayasan Cendekiawan Digital Indonesia, 2025)
The Buntari Ceramic Studio, founded in 2014 in Yogyakarta, was established with a strong sense of cultural responsibility to help safeguard the endangered Pagerjurang pottery tradition. This local heritage is recognized for its distinctive reddish-brown clay and the application of a unique slant-turning technique, which sets it apart from other pottery forms in Indonesia. In recent years, however, the tradition has been facing a serious decline due to the absence of younger generations willing to carry it forward. This research aims to explore the role of Buntari Ceramic Studio in maintaining the continuity and relevance of Pagerjurang pottery in contemporary cultural life. Using a qualitative descriptive method and triangulation of sources, the study finds that the studio actively promotes traditional techniques through educational workshops, collaborative exhibitions, and public engagement. These efforts not only revitalize interest in traditional crafts but also strengthen the identity of local cultural practices. The results offer meaningful insights for cultural sustainability and inspire further studies on heritage preservation.